Judging law and policy : courts and policymaking in the American political system - Howard, Robert M., 1956-; Steigerwalt, Amy, 1976- (New York : Routledge, 2012)
'To what extent do courts make social and public policy and influence social and public policy change? This innovative text analyzes this question generally and in seven distinct policy areas that play out in both federal and state courts--tax policy, environmental policy, reproductive rights, sex equality, affirmative action, school finance, and same-sex marriage. The authors address these issues through the twin lenses of how state and federal courts must and do interact with the other branches of government and whether judicial policy-making is a form of activist judging. Each chapter analysis investigates the current state of the law, the extent of court involvement in policy change, the responses of other governmental entities and outside actors, and the factors which influenced the degree of implementation and impact of the relevant court decisions. Throughout the book, Howard and Steigerwalt examine and analyze the literature on judicial policy-making as well as evaluate existing measures of judicial ideology, judicial activism, court and legal policy formation, policy change and policy impact. This unique text offers new insights and areas to research in this important field of American politics'--
Includes bibliographical references (p. [192]-204) and index.
Keywords: Political questions and judicial power -- United States